Effectiveness of Teacher-Made Learning Package in Teaching Mathematics 4 During the COVID-19 Pandemic - Ayop, Elmar (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study determined the effectiveness of a teacher-made learning package in teaching Mathematics 4 during the COVID-19 pandemic among Grade 4 struggling learners at Domnar Lopez-Copada Integrated IP School, Maasim 3 District, Division of Sarangani Province, during the school year 2021–2022. A single-group pre-test–post-test (pre-experimental) design was employed to measure the effects of the intervention by comparing the pre-test and post-test scores of the learners. Total enumeration was applied to determine the 35 respondents, who were selected because they had mathematics grades below 80 and parents able to provide home-based learning support. The teacher-made learning package, which contained simplified lessons, exercises, and guided activities, was validated by master teachers and supported through Radio-Based Instruction (RBI) and parent orientations prior to its implementation. A validated 30-item test was prepared, pilot-tested, and subjected to item analysis to determine the index of difficulty, and the same instrument was administered as both pre-test and post-test before and after the two-month intervention. Frequency counts, percentages, and a t-test for correlated samples were used to analyze the data. Results revealed that the learners obtained a pre-test mean of 16.8 (56%), described as average, which increased to a post-test mean of 21.3 (71%), described as high. The computed t-value of 10.37 exceeded the tabular value of 1.645, leading to the rejection of the null hypothesis and indicating a statistically significant difference between the pre-test and post-test scores. These findings indicate that the teacher-made learning package was effective in improving the academic performance of Grade 4 struggling learners in Mathematics. The study recommends that the Department of Education, school administrators, teachers, and parents strengthen the development and use of teacher-made learning packages to sustain learning continuity during instructional disruptions.